ANALISIS PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS 1 SD - Yoana Kresensia Br Sirait, Hasria Simanullang (Pondok Pesantren Baitul Qur`an Sambas, 2024)
This research aims to determine the analysis of parental attention to student learning achievement. The research method used is qualitative with a phenomenological approach. Data collection techniques use observation, interviews and documents. The research results show that parental attention has a positive influence on student learning achievement. Parents who give sufficient attention to their children will encourage their children to study harder and improve their achievements and parents provide important motivational encouragement to improve students' learning achievements. They must provide appropriate and sustainable learning motivation so that students remain enthusiastic in learning.